Law and safety in liquidation and dissolution of companies. - Ja. Strémy (Law and Safety)
The purpose of this article is to clarify the process of liquidation and dissolution of companies. The research below defines the rules that must be followed when approaching those procedures in the Kingdom of Spain and Republic of Austria. In those countries there are two types of liquidation. First of them is liquidation of company which is solvent, the second one is liquidation of company that cannot pay its debt. In both cases, there are specific duties which must be obeyed to dissolve the company in legal and safe way.